Evaluation of mechanical and physical properties HDPE/Coffee grounds composites with different filler particles size. - BELLILI, Nadira (Biopolymer Applications Journal, 2024)
Plant-based fiber composites are currently experiencing strong growth due in particular to the growing interest in them from the automotive industry. These fibers present an excellent alternative to glass fibers from an environmental point of view due to their biodegradability and their much more neutral combustibility in terms of the release of harmful gases or solid residues. However, the incorporation of cellulosic materials in the thermoplastic matrix affects a large number of properties. Many factors such as the nature and size of the filler incorporated may influence the properties of composites. This present work consists, to study the effect of the particle size of a natural waste on the mechanical and physical properties of a polymer matrix. Different formulations based on HDPE/ Coffee grounds flour were prepared with loading rate of 20 % and different sizes of coffee grounds flour particles (125, 180 and 250 μm). They were, characterized by mechanical tests using the tensile and the impact test. The Physical properties of composites are, obtained by the density measurement.